PENGARUH LIMBAH CAIR TAHU TERHADAP PERTUMBUHAN POPULASI CHLORELLA PYRENOIDOSA H. CHICK DALAM SKALA LABORATORIUM - Fatmawati Munir; Riche Hariyati; Erry Wiryani (Jurnal Akademika Biologi, 2017)
Chlorella pyrenoidosa H.Chick is one of abundant microalgae in Indonesia and mostly cultivated due to its characters which are fast and easily transplanted. Tofu liquid waste contains nutrient which is needed by mikroalga because it contains inorganic content such as carbon, nitrogen, phosphorus, potassium. This research is to study the influence of difference concentration of tofu liquid waste towards population growth of C. pyrenoidosa and concentration level of  tofu liquid waste towards population growth of C. pyrenoidosa. The method is by cultivating C. pyrenoidosa H.Chick through the water media which has been given any tofu liquid waste concentration which functions as nutrient source for microalgae. The tofu liquid waste concentration  is consisting of0% as control, 15%, 30%, 45% and 60% and it’s conducted by three times repetition.  The obtained data was tested by ANOVA. As the F score was different then continued by Duncan test. The result shows that the optimal peak of microalgae’s population growth could befound in media with 15% concentration of tofu liquid waste, 337.500 cell/ml, then another control(0%), 170.000 cell/ml and 30%, 119.167 cell/ml, 45%, 81.667 cell/ml. The solidity of lowest population in  60%  concentration showed 65.833 cell/ml. This  findings  has showed that thedifferent handling of concentration towards tofu liquid waste has influenced on C. pyrenoidosapopulation growth. The optimal growth reaches at 15% concentration of  tofu liquid waste. Keywords: Chlorella pyrenoidosa, population, waste, liquid, tofu